Features of the Effect of Cataracts and Glaucoma on the Daily Activities of Patients with Sarcopenic Obesity - O. L. Fabrikantov; A. E. Kopylov; N. M. Agarkov (Oftalʹmologiâ, 2024)
Age-associated glaucoma and cataracts in combination with sarcopenic obesity, formed mainly against the background of physical inactivity due to vision deficiency, potentially contribute to a decrease in patients’ activity in everyday life, but the latter has not been studied practically by special tests that take into account visual impairment. The purpose: to study the peculiarities of the effect of cataracts and primary glaucoma on the daily activities of patients with sarcopenic obesity. 125 patients aged 60–74 years with sarcopenic obesity and stage 2 mixed cataract, 138 patients of the same age with sarcopenic obesity and stage 2 primary glaucoma were examined in clinical conditions. The diagnosis of glaucoma and cataracts was performed based on the results of a comprehensive clinical and hardware examination of patients and in accordance with the criteria of the National Guidelines. Sarcopenia was detected using the European working group on sarcopenia in older people scale, and obesity was measured by a body mass index ≥30 kg/m2. The assessment of activities in everyday life was carried out according to a specific test developed by us. A more significant effect of cataracts combined with sarcopenic obesity, causing complete dependence on others (12.18 points) in daily life activities, was found than the effect of glaucoma combined with sarcopenic obesity, causing moderate dependence — 10.18 points (p < 0.01). Patients of the compared groups also have statistically significant differences in all types of activities in everyday life, including threading a needle and cutting nails, which cause the greatest dependence on outside help in their performance. In particular, restrictions on threading a needle in patients with cataracts and sarcopenic obesity have 1.84 ± 0.03 points, which is significantly higher than in patients with glaucoma and sarcopenic obesity (p < 0.01). A similar pattern has been established for nail clipping, the limits for which are 1.75 ± 0.03 points and 1.43 ± 0.04 points, respectively. However, the following ranking places of the considered limitations of activity in everyday life differ statistically significant and in the third position of patients with cataract and sarcopenic obesity is independent writing of the text (1.68 ± 0.04 points), and in patients with glaucoma and sarcopenic obesity — reading of the text — 1.38 ± 0.03 points (p < 0.01). The fourth rank also differs when in patients with cataracts and sarcopenic obesity it corresponds to reading the text (1.53 ± 0.04 points), and in patients with glaucoma and sarcopenic obesity — writing the text — 1.32 ± 0.02 points (p < 0.01). The revealed features of the effect of glaucoma and cataracts combined with sarcopenic obesity should be used by ophthalmologists when forming recommendations on the behavior of patients in everyday life.